The last mountain man eaudiobook Matt jensen series, book 1. - Johnstone, J.A (Matt Jensen: The Last Mountain Man, 2007)
USA Today best-selling author William W. Johnstone is one of the most prolific writers of the past 50 years, with nearly 200 thrilling books to his credit. Matt Jensen, reared by legendary mountain hero Smoke, is the last of a proud breed. He will soon learn that dispensing justice with a gun is the only true way to execute righteous revenge in the Old West.